Leprosy: health education in front of prejudice and social stigms (Research, Society and Development, 2020)
The main objective of this article is to report the experience of nursing students in a health education action on leprosy, with the elderly, in a Municipal Health Unit. The methodology consisted of a qualitative study with a descriptive approach of the type of experience report, having as a basic instrument of elaboration of the research the Arch of Maguerez, which is composed of five stages, namely: a) Observation of Reality; b) Survey of Key Points; (c) theorization; d) Solution Hypotheses; e) Return to Reality. The result was through health education, solving numerous doubts that users had about leprosy, contributing to the promotion and prevention of the population's health, enabling the execution of preventive practices and adherence to treatment. We believe that this study can contribute to other research focused on this approach and serve as an incentive for more health actions on this disease, based on coping with prejudices, taboos and social stigmas, thus fulfilling itself effectively and responsibly.